2022
DOI: 10.3389/fmed.2022.942751
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal chest wall mass and rib osteomyelitis associated with the use of fingolimod: A case report and literature review

Abstract: Being introduced in 2010, fingolimod was among the first oral therapies for relapsing multiple sclerosis (MS). Since that time, postmarketing surveillance has noted several case reports of various cryptococcal infections associated with fingolimod use. To date, approximately 15 such case reports have been published. We present the first and unique case of cryptococcal chest wall mass and rib osteomyelitis associated with fingolimod use. The patient presented with left-side chest pain and was found to have a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The authors stated that bony involvement due to Cryptococcus species is uncommon, with an estimated prevalence of 5%, and virtually every bone could be involved. The current review revealed 106 more cases in adults including this present report [ 4 8 , 11 82 ] (Table 1 ).…”
Section: Review Of the Literaturementioning
confidence: 75%
“…The authors stated that bony involvement due to Cryptococcus species is uncommon, with an estimated prevalence of 5%, and virtually every bone could be involved. The current review revealed 106 more cases in adults including this present report [ 4 8 , 11 82 ] (Table 1 ).…”
Section: Review Of the Literaturementioning
confidence: 75%
“…Of the total number of patients, the male sex was affected in 48 cases while the median age was 60 years, with statistically significant differences between the two groups: alive versus dead in both variables ( p value = 0.0203 and 0.0332, respectively). Of 60 patients with available information, 31 were from the United States 15 , 16 , 19 40 (51.6%), 8 from Peru 41 (13.3%), 7 from Brazil 14 , 42 47 (11.6%), and 2 from India 48 , 49 and Italy 50 , 51 (3.3% each), while the rest were from Canada, 52 Colombia, 53 China, 54 the Czech Republic, 55 the UK, 56 Uganda, 57 Qatar, 58 Lebanon, 59 Spain, 60 and Germany 61 ( n = 1; 1.7% each).…”
Section: Resultsmentioning
confidence: 99%
“…After inhalation, Cryptococcus can localize in the lungs and cause cryptococcal pneumonia or disseminate hematogenously, affecting other extrapulmonary infection sites [ 7 ]. Although the lungs and central nervous system are the most commonly affected sites, other organs or tissues may be infected [ 2 , 3 , 8 ]. Occasionally, the skeleton can also be invaded leading to cryptococcal osteomyelitis, which usually results from the hematogenous spread of lung infection [ 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%